Dampak keberadaan Pelabuhan Perikanan Nusantara Idi Aceh Timur terhadap sosial ekonomi masyarakat nelayan - Insyafrijal Insyafrijal; Muhammad Nasir; Faisal Abdullah (Depik, 2018)
The purpose of this study was to analyze the socio-economic impact of the community as beneficiaries of Idi fishing port (PPN) and to formulate a strategy to increase people's income. The method used in this research is descriptive method and case study, where descriptive method is used to collect data about the condition and activity of Idi fishing port operation within 5 (five) years, while the case study method is used to know the socio-economic condition of the community as the beneficiary ports, where the data were taken are workers within the port area as well as direct or indirect beneficiaries of port activities with a focal point on fishing communities as the largest workers in the port area. Formulation of income generation strategy using SWOT analysis. The results of the study explain that the condition of the community around the of Idi fishery port is not much different from the condition of other coastal communities where education is not the main priority. In addition, the amount of income in general is still strongly influenced by fish production and ship visits and has not yet met the needs of household fishermen's expenditure. Strategies that can be used to increase people's income is through increased efficiency in the preparation of facilities and infrastructure so that the process of fishing and loading and unloading fish can be faster, saving time and saving cost. Further information on the location of fishing ground and encourage the use of frozen freezer on board is recommended to be done so that the cost of fishing is cheaper and fish prices higher. Tujuan penelitian ini adalah untuk  menganalisis dampak sosial ekonomi masyarakat nelayan sebagai penerima manfaat Pelabuhan Perikanan Nusantara (PPN) Idi serta merumuskan strategi peningkatan pendapatan masyarakat. Metode yang digunakan dalam penelitian adalah metode deskriptif dan studi kasus, dimana metode deskriptif digunakan untuk mengumpulkan data mengenai kondisi dan aktivitas operasional  PPN Idi dalam jangka waktu 5 (lima) tahun. Perumusan strategi peningkatan pendapatan masyarakat menggunakan analisis Internal Strengths dan weaknesses serta lingkungan Eksternal Opportunities dan Threats (SWOT). Hasil penelitian menjelaskan bahwa kondisi masyarakat nelayan disekitar PPN Idi tidak jauh berbeda dengan kondisi masyarakat pesisir lainnya dimana pendidikan bukan prioritas utama. Selain itu jumlah pendapatan secara umum masih sangat dipengaruhi oleh produksi ikan serta kunjungan kapal. Strategi yang bisa digunakan untuk meningkatkan pendapatan masyarakat yaitu melalui peningkatan efisiensi dalam penyiapan sarana serta prasarana sehingga proses nelayan berangkat dan bongkar muat ikan bisa lebih cepat, menghemat waktu dan biaya. Selanjutnya informasi lokasi keberadaan ikan secara berkala serta mendorong penggunaan freezer beku diatas kapal direkomendasikan untuk dilakukan sehingga biaya melaut lebih murah dan harga ikan lebih tinggi.